The Asaila depression, an archaeological landscape in Qatar - Drechsler, Philipp; Engel, Max; Brill, Dominik; Gerber, Christoph (Proceedings of the Seminar for Arabian Studies, 2016)
The Asaila region (al-ΚUsaylah) in south-western Qatar comprises a prominent solution-collapse depression filled with Quaternary aeolian sand and surrounding Tertiary limestone plateaus. Intensive systematic field walking in this area led to the identification of a total of 237 localities with evidence of past human activities. Most numerous finds are flint artefact scatters and single pieces of flint artefacts. Based on technological and typological studies, the majority of these artefact assemblages can be related to the Early Neolithic Qatar-B industries and the Middle Neolithic. The conspicuous absence of material remains that can be dated to the time period between the Chalcolithic and the Classical period plausibly suggests a decrease in human activities for more than five millennia. It was not until the Islamic period that the Asaila region became intensively occupied again.